Medical Neglect - a Form of Child Abuse - N.V. Kotova (Zaslavsky O.Yu., 2013)
Medical neglect is the postponement or denial of necessary medical care for child by the parents, which may cause substantial harm to the health of the child and threatened his life. Pediatricians and family physicians should always act in the interests of the child. If parents do not provide adequate care to a child, the health care providers should take a number of actions aimed at identifying and elimination the causes of medical neglect. Health care providers should always choose the best type of intervention to eliminate medical neglect, which ensures the health and safety of the child's life.